2016
DOI: 10.18869/acadpub.ijal.19.1.181
|View full text |Cite
|
Sign up to set email alerts
|

L2 Teachers’ Explicit and Implicit Corrective Feedback and Its Linguistic Focus

Abstract: Various studies have confirmed the influential role of corrective feedback (CF) in the development of different linguistic skills and components. However, little, if any, research has been conducted on comparing types of linguistic errors treated by teachers through CF. To bridge this gap, this study sought to investigate the linguistic errors addressed and the types of CF provided by teachers. To this end, the classes of 40 teachers teaching at the intermediate level were audio-recorded for two successive ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
0
2
Order By: Relevance
“…Since as perceived by their English major students (both from mainstream and ESL classrooms), they were corrected by these teachers in 7 to 9 times per meeting in the class. This is somewhat not congruent with the result of the study conducted by Shirkhani and Tajeddin (2016) on the detailed analysis of around 128 hours of classroom interactions revealing that explicit correction is the most frequent of all oral error corrections.…”
Section: English Teachers' Oral Error Correction Usedcontrasting
confidence: 85%
“…Since as perceived by their English major students (both from mainstream and ESL classrooms), they were corrected by these teachers in 7 to 9 times per meeting in the class. This is somewhat not congruent with the result of the study conducted by Shirkhani and Tajeddin (2016) on the detailed analysis of around 128 hours of classroom interactions revealing that explicit correction is the most frequent of all oral error corrections.…”
Section: English Teachers' Oral Error Correction Usedcontrasting
confidence: 85%
“…However, the findings of the current study do not support the previous research. These results differ from some published studies of Aranguiz and Espinoza (2016) and Shirkhani and Tajeddin (2016) which found out that teachers prefer to use explicit correction as the most frequent strategy. It seems that students' tendency toward teacher-generated explicit types of corrective feedback and teachers' preferences for implicit feedback fostering self-correction is a recurring theme in the corrective feedback literature as it has been arrived at by some previous studies (Amrhein and Nassaji, 2010;Brown, 2009;Han & Jung, 2007;Lee, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Looking at the connection between errors and explicit corrections, this study discloses that both L1 and L2 explicit corrections were offered to treat students' phonological errors most of the time. Regardless of the language use to promote explicit correction, the present study is in line with Shirkhani and Tajeddin's study which found that explicit corrective feedback (in which explicit correction is a part of explicit corrective feedback) was frequently used to correct students' pronunciation errors [30]. This can be inferred that explicit correction is an appropriate strategy to fix errors related to either phonology or pronunciation.…”
Section: When Correcting Students' Oral Errors I Use Both Indonesia supporting
confidence: 90%
“…Since phonological errors have the highest frequency, this means that students found English pronunciation difficult. Similar to this finding, Shirkhani and Tajeddin's study identified that errors in pronunciation were mostly produced by students [30]. The occurrence of the errors might be affected by some linguistic factors.…”
Section: A Errors Committed By Studentssupporting
confidence: 65%